CHANGES OF PHYSICAL STRESS TOLERANCE IN PATIENTS WITH ACUTE MYOCAQRDIAL INFARCTION UNDER THE INFLUENCE OF MILLIMETER-LENGTH WAVES - V. Y. Ushakov (Российский кардиологический журнал, 2001)
The aim of the study was to evaluate the influence of millimeter-length waves on the functional condition of patients with acute myocardial infarction as established by veloergometry.We have studied 95 patients with acute myocardial infarction, divided into 3 groups depending on the mode of treatment: 55 with radiation in conjunction with conventional treatment, the control group of 30 with conventional treatment only and the placebo group of 14.The basic group demonstrated reliably higher tolerance to physical stress as compared to the control and placebo group after 30 and 60 days.